Empowering Nagari Women's Groups by Enhancing the Creative Economy through Traditional Weaving in Nagari Batu Hampar - Sofia Rida; Muhammad Taufik; Muhamad Rezi (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to empower Nagari women's groups in Nagari Batu Hampar by strengthening the creative economy through traditional weaving skills. The main problems facing the community are limited family economic independence, limited productive skills, and suboptimal use of local natural resources, such as pandan (mansiang). The service method is participatory action research, comprising the stages of need assessment, planning, action, and reflection. The activities include focus group discussions (FGDs), socialization on the creative economy, training in traditional and knitted weaving, and sustainable mentoring. The results of the service show an increase in women's knowledge and skills in producing economically valuable woven products, a shift in attitudes from consumption to production, and a growth in collective awareness to develop businesses grounded in local wisdom. This activity strengthens women's economic independence and can be replicated in other rural areas.